2016
DOI: 10.1080/15548627.2016.1256523
|View full text |Cite
|
Sign up to set email alerts
|

A functional nanocarrier that copenetrates extracellular matrix and multiple layers of tumor cells for sequential and deep tumor autophagy inhibitor and chemotherapeutic delivery

Abstract: To further enhance the intensity of deep tumor drug delivery and integrate a combined therapy, we herein report on a core-shell nanocarrier that could simultaneously overcome the double barriers of the extracellular matrix (ECM) and multiple layers of tumor cells (MLTC). A pH-triggered reversible swelling-shrinking core and an MMP2 (matrix metallopeptidase 2) degradable shell were developed to encapsulate chemotherapeutics and macroautophagy/autophagy inhibitors, respectively. MMP2 degraded the shell, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…To deliver chemotherapeutic agents into the deep tumor, Wang et al designed a core-shell nanocarrier in which the reversible swelling-shrinking core was loaded with an anticancer drug (DOX) and the degradable gelatin shell was used to encapsulate the autophagy inhibitor 3-methyladenine (3-MA). [73] The gelatin shell could be degraded by the overexpressed MMP-2 in the tumor region to release the encapsulated 3-MA. Then, the exposed small core could become larger upon exposure to the acidic lysosome environment of cancer cells, ultimately resulting in the rapid release of DOX to effectively kill the autophagy-inhibited cancer cells.…”
Section: Nss With Multiple Transformationsmentioning
confidence: 99%
“…To deliver chemotherapeutic agents into the deep tumor, Wang et al designed a core-shell nanocarrier in which the reversible swelling-shrinking core was loaded with an anticancer drug (DOX) and the degradable gelatin shell was used to encapsulate the autophagy inhibitor 3-methyladenine (3-MA). [73] The gelatin shell could be degraded by the overexpressed MMP-2 in the tumor region to release the encapsulated 3-MA. Then, the exposed small core could become larger upon exposure to the acidic lysosome environment of cancer cells, ultimately resulting in the rapid release of DOX to effectively kill the autophagy-inhibited cancer cells.…”
Section: Nss With Multiple Transformationsmentioning
confidence: 99%
“…developed nanocarriers composed of a pH‐triggered reversible swelling‐shrinking core to encapsulate DOX and an MMP2‐cleavable gelatin shell to load 3‐methyladenine (3‐MA) which is an autophagy inhibitor because autophagy compromised the antitumor efficacy of DOX. They showed that 3‐MA released at the ECM and entered tumor cells to inhibit their autophagy after MMP2‐induced degradation of the shell, then the exposed core could diffuse along the pores of ECM to deliver DOX into deep tumors . They attempted to explore the role of autophagy in breast cancer metastasis and developed tumor‐activatable particles to co‐deliver DOX and autophagy inhibitor chloroquine phosphate (CQ), termed D/PSP@CQ/CaP.…”
Section: Nanocarriersmentioning
confidence: 99%
“…In a study conducted by Wang et al [327] a nanocarrier was used that could simultaneously overcome the double physiological barriers of tumors. The nanocarrier was designed as a pH-triggered reversible swelling-shrinking core and a matrix metallopeptidase 2 (MMP2) degradable shell for co-delivery of chemotherapeutics DOX and autophagy inhibitors (3-MA).…”
Section: Co-delivery Of Autophagy Inducers/inhibitors and Chemothmentioning
confidence: 99%